História das práticas de interferência da política no meio ambiente das populações ribeirinhas em Manaus e Programa Social e Ambiental dos Igarapés de Manaus - PROSAMIM: do “Barriga d'água” ao sujeito resiliente - Mota, Guilherme Gustavo Vasques (2019)
The Social and Environmental Program of the Manaus Igarapés (PROSAMIM) was implemented through agreements between local governments, the State of Amazonas and the Municipality of Manaus and the Inter-American Development Bank (IDB), a multilateral and regional financing institution whose central target are the hydrographic basins of Educandos and São Raimundo, localities in which, for more than a century, riverside populations were allocated, contingents coming from the great migrations that resisted any and all standard imposed by politics in the periods of the outbreak of two economic cycles: cycle and the Free Zone of Manaus. However, the presence of the riverine populations in the main areas of river and igarapé river in Manaus practically ended with the implementation of PROSAMIM in 2006, a program oriented by the notion of sustainable development. In order to question the practices of the program from the point of view of power relations, and also to answer that factors present in PROSAMIM determined the definitive neutralization of the riparian populations in Manaus, this thesis adhered to the genealogy of Michel Foucault, by the authorities in Manaus alongside riverine populations, not as ways of pacifying a war, but as a continuation of the war against the riverside, perpetrated by other means.With a focus on the discontinuity of practices and the notion of device, the genealogy provided the research, analyze the exercise of power that sought to neutralize resistances of the riverside population in three moments prior to PROSAMIM - in Belle Époque, a period of modernization of Manaus initiated by the Eduardo government Ribeiro, at the beginning of the 20th Century, in the deactivation of the floating city by the military in 1964 and, finally, in the Manaus Moderna Project implemented in 1986. The first practices were related by the thesis to the state reason, moment of the installation of the sovereign power of the Portuguese crown, going through the modernization of the city until the construction of the security device and the effectiveness of its practices in the containment of epidemics by the medical policy in Manaus. Next, the research focused on the practices that guided and determined the deactivation of the floating city by the military, and the publication of Jornal do Commercio about a kind of social enemy coming from the riverside population, the so-called "Water Bellies" or "Water Rats", a notion produced by the speeches of the "medicalized court" and that denounced the profile of the inhabitants of the floating city as abnormal. Neoliberalism is studied as a political rationality that suffered from discontinuities, starting from the neoclassical reasoning, origin related to the Manaus Modern Project, and then ecological thinking with the construction of the environment and the concept of sustainability, PROSAMIM origins. In the end, it was possible to demonstrate that PROSAMIM is a program that makes effective the environment device from practices to create entrepreneurship, sustainability and resilience for human development oriented training, a re-sizing of the pastorate in the control society to produce monitors themselves, definitively neutralizing the riparians and transforming the "water gullet" and the "water rats" into resilient persons